Perception towards Competence (Study in Master’s Study Program of English Language Education, Teacher Training and Education Faculty, Tanjungpura University) - Sudarsono Sudarsono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
The present research was designed to investigate how the students of the Master’s Study Program of English Language Education perceived their lecturers’ competencies. They were pedagogical, professional, personal, and social competencies. The data were collected from 24 students from the relevant study program through a questionnaire. The data were analysed with simple statistics. The research showed that most students perceived their lecturers’ competencies ‘good’ to ‘very good’. Of the 4 competencies investigated, the highest perception was given by the students to personality competency and the least was the social competency. These findings could be inferred that the students paid very good attention to their lecturers during their teaching-learning activities.